Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
3x+ y=-6 substitute "x" for 0
3(0) + y=-6
y= -6
3x+y= -6
substitute "y" for 0
3x+0= -6
--- -----
3 3
x= -2
slope is -3
3(0) + y=-6
y= -6
3x+y= -6
substitute "y" for 0
3x+0= -6
--- -----
3 3
x= -2
slope is -3
Re-arrange so y is subject of formula:
y = -6 - 3x
y = -3x - 6
y = mx + c
c is y intercept and m is gradient (slope)
so, slope is -3, y intercept is -6.
To find the x intercept, you need to find what x is when y is 0, so substitute:
0 = -3(x) -6
Re-arrange
6 = -3 (x)
6 ÷ -3 = x
- 2 = x intercept
so y intercept =-6, slope = -3 , x intercept = -2
y = -6 - 3x
y = -3x - 6
y = mx + c
c is y intercept and m is gradient (slope)
so, slope is -3, y intercept is -6.
To find the x intercept, you need to find what x is when y is 0, so substitute:
0 = -3(x) -6
Re-arrange
6 = -3 (x)
6 ÷ -3 = x
- 2 = x intercept
so y intercept =-6, slope = -3 , x intercept = -2
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.